Trends in Augmented Reality Integration in Biology Learning 2020-2025: A Literature Review - Erma fitriyana; Febby Apriani; Nabila Khaerunnisa (Indonesian Journal of Applied Science and Technology, 2026)
Advancements in digital technology are driving innovation in biology education through the use of Augmented Reality (AR). This literature review analyzes trends regarding the integration of AR into biology instruction between 2020 and 2025. Data were gathered by searching for scholarly articles on Google Scholar based on specific inclusion criteria, resulting in 20 relevant articles that were analyzed descriptively. The findings indicate that publications on AR integration have steadily increased, peaking in 2024. The most widely used platforms are Android-based AR applications and Assemblr Edu, with content focusing on abstract concepts such as cell structures, organ systems, and physiological processes. The use of AR has been shown to positively impact students' conceptual understanding, motivation, learning outcomes, and digital literacy. However, the implementation of AR still faces technical challenges related to device specifications, internet connectivity, data usage, and teachers' digital proficiency. Overall, AR holds significant potential as an interactive and contextual medium for biology education.